Polysaccharide K and Coriolus versicolor Extracts for Lung Cancer: A Systematic Review. (May 2015) - Fritz, Heidi; Kennedy, Deborah A.; Ishii, Mami; Fergusson, Dean; Fernandes, Rochelle; Cooley, Kieran; Seely, Dugald
Background . Polysaccharide K, also known as PSK or Krestin, is derived from the Coriolus versicolor mushroom and is widely used in Japan as an adjuvant immunotherapy for a variety of cancer including lung cancer. Despite reported benefits, there has been no English language synthesis of PSK for lung cancer. To address this knowledge gap, we conducted a systematic review of PSK for the treatment of lung cancer. Methods . We searched PubMed, EMBASE, CINAHL, the Cochrane Library, AltHealth Watch, and the Library of Science and Technology from inception to August 2014 for clinical and preclinical evidence pertaining to the safety and efficacy of PSK or other Coriolus versicolor extracts for lung cancer. Results . Thirty-one reports of 28 studies were included for full review and analysis. Six studies were randomized controlled trials, 5 were nonrandomized controlled trials, and 17 were preclinical studies. Nine of the reports were Japanese language publications. Fifteen of 17 preclinical studies supported anticancer effects for PSK through immunomodulation and potentiation of immune surveillance, as well as through direct tumor inhibiting actions in vivo that resulted in reduced tumor growth and antimetastatic effects. Nonrandomized controlled trials showed improvement of various survival measures including median survival and 1-, 2-, and 5-year survival. Randomized controlled trials showed benefits on a range of endpoints, including immune parameters and hematological function, performance status and body weight, tumor-related symptoms such as fatigue and anorexia, as well as survival. Although there were conflicting results for impact on some of the tumor-related symptoms and median survival, overall most randomized controlled trials supported a positive impact for PSK on these endpoints. PSK was safely administered following and in conjunction with standard radiation and chemotherapy. Conclusions . PSK may improve immune function, reduce tumor-associated symptoms, and extend survival in lung cancer patients. Larger, more rigorous randomized controlled trials for PSK in lung cancer patients are warranted.